Bus network redesigns and public transit equity analysis: Evaluating system-wide changes in Richmond, Virginia. (April 2023) - Liu, Haijing; Rahman, Mashrur; Karner, Alex
Highlights: The equity effects of bus network redesigns (BNRs) are poorly understood. We use a controversial BNR to demonstrate different equity analysis approaches. Methodological decisions and analytical parameters affect equity determinations. The redesign is largely equitable, but overall access levels remain low. Off-peak times, baseline access, and percentage changes must all be assessed. Abstract: Public transit agencies around the world are increasingly using bus network redesigns (BNRs) to address ongoing ridership declines, but little is known about the equity impacts of these redesigns on vulnerable populations most likely to use transit to meet their daily needs. Despite Federal Transit Administration requirements for public transit agencies to assess the equity impacts of major service changes (like BNRs), analysis results are often perfunctory and unsatisfying. The academic literature has also proposed and evaluated many different performance measures in the context of equity evaluations. In this paper, we investigate a controversial BNR undertaken in Richmond, Virginia. During the planning and implementation process, different analysts reached different conclusions about potential impacts. We employ different performance measures, including service area and access changes, to show that the redesign is largely equitable but baseline levels of accessibility for vulnerable groups remain low. We also argue that a complete understanding of BNR impacts requires examining off-peak times. Meaningful public engagement is crucial for any equity analysis since the results can change substantially depending on the chosen parameters, and these parameters should be chosen by those most affected by a BNR.